Plasmacytoid dendritic cell dichotomy: identification of interferon-α producing cells as a phenotypically and functionally distinct subset - Björck, Pia (2010)
Plasmacytoid dendritic cells (pDC) produce large amounts of type I interferon in response to invading pathogens, but can also suppress immune responses and promote tolerance. Here we show that in mice these functions are attributable to two distinct pDC subsets, one of which gives rise to the other. CD9(pos) Siglec-H(low) pDC secrete interferon-α (IFN-α) when stimulated with Toll-like receptor (TLR) agonists, induce cytotoxic T lymphocytes (CTLs) and promote protective anti-tumor immunity. By contrast, CD9(neg) Siglec-H(high) pDC secrete negligible amounts of IFN-α, induce FoxP3+ CD4+ T cells and fail to promote anti-tumor immunity. Although newly formed pDC in the bone marrow (BM) are CD9(pos) and are capable of producing IFN-α, after these cells traffic to peripheral tissues they lose CD9 expression and the ability to produce IFN-α. We propose that newly generated pDC mobilized from the BM, rather than tissue-resident pDC, are the major source of IFN-α in infected hosts.